What Can Complex Dietary Supplements Do for Hair Loss and How Can It Be Validly Measured—A Review - Nicole Braun; Ulrike Heinrich (Applied Sciences, 2020)
Hair plays a major role in perception within a society. It provides information about gender, age, health, and social status. It is therefore not surprising that those affected are exposed to great suffering due to the widespread occurrence of hair loss. As a result, the demand for new products to remedy this problem is not diminishing. Hair grows in cycles, and a hair follicle goes through several phases called the hair cycle. The active growth phase (anagen phase) lasts 2–6 years. In this state a hair follicle shows a growth of about 1 cm per month. In order to improve the existing hair status, hair should be kept in the active anagen phase as long as possible, or the transition to anagen should be stimulated. A number of reviews already describe the influence of individual active ingredients on hair growth. However, the following review describes existing studies of complex dietary supplements with their experimental weaknesses and strengths and their influence on hair loss. Also, for the determination of hair loss, it is important to use a valid method with high acceptance by the test persons. In this context, the TrichoScale® is a validated and non-invasive tool for quantifying hair loss/hair growth. Thus, it is an ideal measuring instrument to objectively quantify the effectiveness of a hair loss treatment.